Purchasing Guide - Berry, Harold A. (Pontiac, Mich. : Ameritech Industrial Purchasing Guides, 1991)
The material may be of interest as a reference book for purchasing students, or could be included in the studies of a general business student when purchasing courses are not taught.
Title from cover.
aia 06/02/2019
Loans
Keywords: Manufactures; Connecticut